Natural Transmission of Bat-like Severe Acute Respiratory Syndrome Coronavirus 2 Without Proline-Arginine-Arginine-Alanine Variants in Coronavirus Disease 2019 Patients. (10th July 2020) - Wong, Yik Chun; Lau, Siu Ying; Wang To, Kelvin Kai; Mok, Bobo Wing Yee; Li, Xin; Wang, Pui; Deng, Shaofeng; Woo, Kin Fai; Du, Zhenglong; Li, Cun; Zhou, Jie; Chan, Jasper Fuk Woo; et al.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contains the furin cleavage Proline-Arginine-Arginine-Alanine (PRRA) motif in the S1/S2 region, which enhances viral pathogenicity but is absent in closely related bat and pangolin coronaviruses. Whether bat-like coronaviral variants without PRRA (∆PRRA) can establish natural infections in humans is unknown. Methods: Here, we developed a duplex digital polymerase chain reaction assay to examine ∆PRRA variants in Vero-E6-propagated isolates, human organoids, experimentally infected hamsters, and coronavirus disease 2019 (COVID-19) patients. Results: We found that SARS-CoV-2, as currently transmitting in humans, contained a quasispecies of wild-type, ∆PRRA variants and variants that have mutations upstream of the PRRA motif. Moreover, the ∆PRRA variants were readily detected despite being at a low intra-host frequency in transmitted founder viruses in hamsters and in COVID-19 patients, including in acute cases and a family cluster, with a prevalence rate of 52.9%. Conclusions: Our findings demonstrate that bat-like SARS-CoV-2ΔPRRA not only naturally exists but remains transmissible in COVID-19 patients, which has significant implications regarding the zoonotic origin and natural evolution of SARS-CoV-2. Abstract : Using a specific digital PCR assay, we discovered the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants carrying mutations upstream and at the S1/S2 site in COVID-19 patients. Bat-like SARS-CoV-2ΔPRRA variants naturally exist and remain transmissible in humans.